Between police work and warfare: transformations in the scope of Lima's police forces (1827-1838) - Ríos Rodríguez, Carlos Jesús (2020)
The main aim of this article is to examine the formation of the Peruvian state through analysis of the shifting quantitative dimensions of the army's police forces assigned to the department of Lima during the first years of the republican era. It can be argued that those police forces were weakened or suppressed in the context of war in order to incorporate their personnel into the forces of the caudillos who were preparing to march onto the battlefields, thereby demonstrating that in Peru wars weakened the state's coercive capacity with regard to public security during the early republican period.